Inputs of heavy metals and rare earth elements in soils via phosphate fertilizers and correctives - SILVA, Fernando Bruno Vieira da (2018)
Phosphate fertilizers and corrective are significant sources of soil contamination by heavy metals and rare earth elements, and long-term cultivated soils can accumulate heavy metals above the maximum permissible limits. In this sense, the objectives of the study were (i) to evaluate the potential contamination of Brazilian soils by heavy metals and rare earth via phosphate fertilizers and corrective; (ii) to evaluate the accumulation of heavy metals in soils intensively cultivated with sugarcane, as well as to identify the possible sources of contamination. Initially, were performed total digests of 53 representative samples of P-containing fertilizers and commercialized in Brazil. Concentrations of As, Cd, Cr, Hg and Pb were investigated in fertilizers, which are elements regulated by national legislation. Also the additions of these metals to Brazilian soils were estimated based on the annual consumption and the average concentrations verified in each product. Subsequently, 60 samples of surface soils from areas cultivated with sugarcane were collected, these areas had a long history of use. In the soils, the environmentally available metals (Cd, Cr, Cu, Ni, Pb and Zn) were evaluated, as well as the physico-chemical characterization. The contents of metals in the soils were compared with the guiding values of quality; correlated with soil properties and; subjected to multivariate statistical analyzes to trace the origin of the metals. Finally, the total and soluble concentrations of Ce, La, Nd, Pr, Sm, Sc, Eu, Y, Dy, Gd, Yb, Er, Tb, Ho and Lu were investigated in 60 supplies samples (phosphate fertilizer, and limestone) used in Brazilian agriculture. In addition, the contributions of these elements to Brazilian soils were estimated through the use of phosphate fertilizers and soil correctives. The results of the study showed that Cd in phosphate rocks are the most worrisome, and that in the medium term the heavy metals present in fertilizers containing P do not represent environmental risk. However, the intensive application of phosphate fertilizers in soils cultivated with sugarcane promoted the accumulation of Cd above the guiding values of quality, and in some cases the soils represented a potential risk to human health. With regard to rare earths, it was observed that the solubility of these elements in phosphate fertilizers is dependent on the raw material used in industry (igneous or sedimentary). The annual additions of these elements to Brazilian soils are > 4000 t year-1 and that Ce, La, Nd and Y are the most worrisome. Limestone proved to be a significant source of Gd for agricultural soils. Therefore, soils that continuously receive high doses of these inputs are probably enriched with ETRs.